When Leadership and Climate Matter: Enhancing Teachers’ Work Ethic through Participative School Leadership - Soim Soim; Eko Sigit Purwanto; Nik Haryanti (Indonesian Journal of Education and Social Studies, 2026)
Teachers’ work ethic is a crucial factor in supporting instructional quality and the achievement of educational goals. Variations in teachers’ work ethic across schools indicate that organizational factors play a significant role in shaping teachers’ professional attitudes and behavior. This study aims to obtain empirical evidence on the influence of the principal’s participative leadership style and school climate on teachers’ work ethic. The research employed a quantitative approach with an explanatory survey design. The population consisted of 142 teachers, with 105 teachers selected as respondents. Data were collected through a structured questionnaire developed based on theoretical indicators of participative leadership, school climate, and teachers’ work ethic. Multiple linear regression analysis was used to analyze the data with the assistance of SPSS software. The results reveal that the principal’s participative leadership style has a positive and significant effect on teachers’ work ethic. In addition, school climate also has a positive and significant influence on teachers’ work ethic. Simultaneously, participative leadership style and school climate significantly contribute to enhancing teachers’ work ethic. These findings indicate that involving teachers in decision making and creating a supportive, harmonious, and conducive school environment can strengthen teachers’ motivation, responsibility, and professional dedication. This study provides important implications for school principals and educational policymakers to implement participative leadership practices and foster a positive school climate as effective strategies for improving teachers’ work ethic and overall educational quality.